Longitudinal associations between sleep duration and cognitive impairment in Chinese elderly - Chen, Wei-chao; Wang, Xiao-yan (Frontiers in Aging Neuroscience, 2022)
Background: Age-associated cognitive decline has become a major threat to both personal welfare and public health and can further develop into Dementia/Alzheimer’s disease. Sleep is significantly correlated with cognitive function, but both cognitive impairment and sleep problems increase with normal aging. This study explored how sleep duration affects cognition performance among older adults in China. Results: The empirical study showed a U-shaped relationship between sleep duration and increased risk of cognitive impairment. Short and long sleep durations were positively associated with cognitive impairment. Tests of interactions between sleep duration and sleep quality showed that short sleep durations with fair sleep quality had an increased risk of cognitive impairment. Further, the participants were divided into two groups: normal cognition and mild cognitive impairment (MCI, 18 ≤ MMSE score ≤ 24) at baseline. First, of the participants with normal cognition at baseline, those who sleeping >7 hours at follow-up and >7 hours at both baseline and 4-year follow-up assessments could increase the risk of cognitive impairment. Second, for individuals with MCI at baseline, those who transitioned to sleeping >7 hours at follow-up period and >7 hours at both baseline and 4-year follow-up assessments had a lower chance of reverting to normal cognition.